Hot electron retention in laser plasma created under terawatt subnanosecond irradiation of Cu targets. (5th October 2020) - Pisarczyk, T; Kalal, M; Gus'kov, S Yu; Batani, D; Renner, O; Santos, J; Dudzak, R; Zaras-Szydłowska, A; Chodukowski, T; Rusiniak, Z; Dostal, J; Krasa, J; et al.
Abstract: Laser plasma created by intense light interaction with matter plays an important role in high-energy density fundamental studies and many prospective applications. Terawatt laser-produced plasma related to the low collisional and relativistic domain may form supersonic flows and is prone to the generation of strong spontaneous magnetic fields. The comprehensive experimental study presented in this work provides a reference point for the theoretical description of laser-plasma interaction, focusing on the hot electron generation. It experimentally quantifies the phenomenon of hot electron retention, which serves as a boundary condition for most plasma expansion models. Hot electrons, being responsible for nonlocal thermal and electric conductivities, are important for a large variety of processes in such plasmas. The multiple-frame complex-interferometric data providing information on time resolved spontaneous magnetic fields and electron density distribution, complemented by particle spectra and x-ray measurements, were obtained under irradiation of the planar massive Cu and plastic-coated targets by the iodine laser pulse with an intensity of above 10 16 W cm −2 . The data shows that the hot electron emission from the interaction region outside the target is strongly suppressed, while the electron flow inside the target, i.e. in the direction of the incident laser beam, is a dominant process and contains almost the whole hot electron population. The obtained quantitative characterization of this phenomenon is of primary importance for plasma applications spanning from ICF to laser-driven discharge magnetic field generators.